(untitled) (Research, Society and Development, 2022)
Objective: to describe the technique of making an epithesis in acrylic, to restore aesthetics and self-esteem of patients with periodontal tissue loss, in a simple and fast way. Methodology: A case report. Perform an impression with alginate, make an individual tray and obtain the working model. Performing the diagnostic wax-up, acrylization and intra oral installation. Results: The treatment, little known by clinicians, restored the patient’s smile and self-esteem safely and quickly. Conclusion: The gingival epithesis in heat-curable acrylic offers a quick, accurate, non-invasive and simple technique that allows the patient to be rehabilitated with esthetics, comfort, good adaptation and low cost.